Persistent Nasal Skin Lesions in Pemphigus Patients and the Role of Methotrexate in Treatment: A Case Series Study - Kavyani , Mohamad Reza; Daneshpazhooh, Maryam; Heidari, Sama; Esfahani, Navid Namakizadeh; Ahmadian , Sarina; Azizpour, Arghavan; Balighi, Kamran (Dermatology Practical & Conceptual, 2025)
Introduction: Nasal involvement might infrequently happen and some lesions may not respond to conventional treatments. Objectives: The current case series report aims to describe the characteristics of 10 confirmed pemphigus vulgaris (PV) and pemphigus foliaceus (PF) patients with nasal skin lesions who did not respond to conventional treatment options or relapsed after a while and to evaluate the role of methotrexate in treatment. Methods: Data regarding patient demographics, disease type and severity, nasal lesion characteristics, and treatment response was obtained from medical records and direct communication with patients between 2019 and 2023. Results: Eight patients received intravenous rituximab (RTX) and 3 methotrexate. Out of the 8 pemphigus vulgaris (PV) patients who underwent RTX treatment, a total of 18 treatment sessions were carried out. Following RTX therapy, significant improvements in the nasal lesions were observed after 11 (61.1%) sessions, with 8 patients (44.4%) achieving complete resolution within 6 months. Additionally, 3 patients who did not have satisfactory results after RTX treatment, received methotrexate, and all of them experienced complete recovery of their nasal lesions within the same time frame. Conclusions: All the patients who benefited from methotrexate never experienced complete remission of their nasal lesions before. It seems methotrexate can be an eligible choice for recalcitrant cases.